Т.СЕЙТЖАНОВ ПОЭМАЛАРЫНЫҢ КӨРКЕМЛИК ӨЗГЕШЕЛИГИ - Ктайбекова, З.; Қырқбаева, У. (ILIM hám JÁMIYET, 2022)
This article talks about poems, considered a lyric-epic genre in Karakalpak literature. The ideological-theatrical, genre and artistic features of the poems are analyzed on the example of the works of the famous Karakalpak poet T. Seytjanov. Poet T. Seytjanov’s poems on the fate of women, love, World War II are interpreted with artistic skill.